The Comparison of Different Diatom Digestive Method using HCl-H2O2 and HCl -KMnO4 in Telaga Pengilon Dieng - Christopher Hardian Widyanta; Tri Retnaningsih Soeprobowati; Jumari Jumari; Riche Hariyati (Indonesian Society of Limnology, 2020)
Identification diatom has been applied as an important key to tracing paleoenvironmental conditions. The knowledge for diatom extraction from sediment is continuing, but the diatom digestive methods in the tropical area is still limited. Telaga Pengilon, located in Dieng Indonesia, is rich in organic material in the sediment, the sample also associates with epiphytic and benthic diatom. Therefore, extracting pure diatom frustules free of organic matter from the sediments is essential for this application. To find the appropriate method for extracting diatoms in Telaga Pengilon, this research compares HCl with H2O2 and HCl with KMNO4 as the digestive reagent. Based on the statistical result (HCl, KMnO4) less time consumed than (HCl, H2O2) during the digestive process (p<0.05) and produced the same amount of residue (p> 0.05). For Pinnularia and Frustulia, the majority of diatoms could be extracted using both methods. Under microscopy, the structure of diatoms remained almost perfect after digestion with H202, the striae clearly visible and the residue digested correctly. Another method using HCl, KMnO4 fragmentation was found for some Pinnularia, and for Frustulia, the striae are clearly visible. This study demonstrated that different diatoms have different resistance for reagents and some of the locations need different reagents because different materials are contained in the sediment and need help to remove material organically. As far as the HCl and H2O2 are appropriate digestion methods in a tropical area such as Telaga Pengilon, HCl, KMnO4 can be a substitute for the less time-consuming process.